Men in Our Lives - Vaghela, Dr. Joyce Felicia (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2019)
Background: Everybody has read about girls, moms and wives. It’s time to read & learn something about men. The men in our lives are ‘unsung heroes’. A good father is one of the most unsung, un-praised and unnoticed and yet one of the most valuable asset in our society. It is with gratitude and a challenge to understand ‘MEN’ in our lives, that this paper is written. Our hypothesis is that in India I. Fifty percent of adult males (1) are married; (2) have female friends; (3) are healthy; (4) burdened with the responsibilities; (5) enjoy games, hobbies and touring etc. II. 20% of males are addicted to one or the other substances and III. To study the Sexual-orientation of men. Methods: It is a cross-sectional study carried out over a period of one month from 23rd April to 22nd May 2018, at field practice area of the Department of Community Health, of a tertiary care hospital in Delhi. The study includes 53subjects (males) within the age group of 21 - 66 years. A pretested questionnaire including the socio-demographic profile, marital & health status, hobbies was used as a study tool to achieve the objectives of the study. Results: The study shows that 27 (50.94%) out of 53 men were married, there were 26 (49.06%) men who had female friends. Men who were healthy were 47 (88.68%). Forty five (84.9%) of men were burdened with some or the other responsibilities. 27 (50.94%) men enjoy movies and games & sports like cricket. Forty seven (88.68%) men have toured in India but only 7(13.21%) have been to foreign countries. Addiction was found in 10 (18.87%). Five (9.43%) were bisexual, 1(1.89%) was homosexual, whereas 7 (13.21%) subjects did not disclose their sexual orientation. Conclusion: Men do have lots of responsibilities yet try to keep healthy by taking interest in games and hobbies. More studies could be conducted on men folk.